The multiple myeloma treatment landscape: international guideline recommendations and clinical practice in Europe - Cavo, Michele; Terpos, Evangelos; Bargay, Joan; Einsele, Hermann; Cavet, Jim; Greil, Richard; De Wit, Edwin (Expert Review of Hematology, 2018)
Introduction: Guidelines provide recommendations on the management of multiple myeloma (MM), but there are no standard algorithms for the choice and sequencing of treatments. As a result, there is widespread variation in the interpretation and implementation of these guidelines. Areas covered: This review will cover: the real-world data on MM treatment patterns; the approved agents available for the treatment of MM; a comparative summary of the national and international clinical guidelines; a discussion on the impact reimbursement decisions have on treatment availability. Expert commentary: In the future, treatment choices may become even more complex as clonal heterogeneity is better understood in the context of response to treatment, and next-generation agents become available. Although information on real-world practice patterns can provide further guidance, to date, few studies have generated data on patients treated with the newer agents in real-world settings. Furthermore, the translation of guideline recommendations into clinical practice across Europe is inconsistent. Additional real-world data are therefore vital to understanding current clinical practice patterns, so that new agents can be effectively incorporated into existing treatment strategies. Such information may aid the development of better guidance, which will ultimately help to ensure that patients receive the best possible care.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Clinical practice; guidelines; multiple myeloma; real-world evidence; treatment sequence